Trends in Clostridioides difficile infection prevalence among pediatric cancer patients: A systematic review and meta-analysis - Muluneh Assefa; Sirak Biset; Azanaw Amare; Wesam Taher Almagharbeh; Getu Girmay; Mitkie Tigabie (PLoS ONE, 2025)
Introduction Pediatric cancer patients are highly susceptible to Clostridioides difficile infection (CDI) due to immunosuppression, prolonged hospitalization, and antibiotic exposure. This study determined the global pooled prevalence of CDI among pediatric cancer patients. Methods According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, 20 available articles published between 1985 and 2024 were included in this study. The extracted data from the relevant articles were analyzed using STATA version 17.0. The effect size estimate was computed using a random-effects model, considering a 95% confidence interval. The I2 statistic and Galbraith plot were used to confirm heterogeneity. Univariate meta-regression, sensitivity, and subgroup analyses were conducted to identify the source of heterogeneity. Egger’s test and a funnel plot were used to check for publication bias. Results The pooled prevalence of CDI was 15.41% (95% CI: 10.57–20.24%), with high heterogeneity (I2 = 99.90%) and statistical significance (p < 0.001). The trend in the study year was a minimum prevalence of 0.96% in 2016–2020 (Brazil) and a maximum prevalence of 38.26% in 2007–2017 (USA). In the subgroup analysis, a relatively high prevalence of CDI was observed in Asia (23.23%; 95% CI: 17.44–29.01%) and prospective studies (20.64%; 95% CI: 14.25–27.03%), and studies included pediatric patients with hematologic, solid tumors, and hematopoietic stem cell transplantation recipients (18.34%; 95% CI: 8.05–28.63%). The test of group differences (p < 0.001) in the continent in subgroup analysis and sample size (p = 0.049) in univariate meta-regression were sources of heterogeneity between the effect sizes of the individual studies. Conclusion There is a significant burden of CDI in pediatric cancer patients. These findings highlight the need for regular detection and targeted treatment of CDI, including drug-resistant strains, in cancer patients to minimize severe complications and mortality.